Evaluating the phototherapy practice and adherence to guideline in managing neonatal hyperbilirubinemia in an Indonesian tertiary referral hospital - Mahendra Tri Arif Sampurna,; Mapindra MP,; Mahindra MP,; Suhargo M,; Etika R,; Utomo MT,; Handayani KD,; Angelika D,; Ayuningtyas W,; Efendi F,; Cheah FC, (Penerbit Universiti Kebangsaan Malaysia, 2024)
A guideline for the management of hyperbilirubinemia in infants has recently been established in Indonesia, but physician acceptance and adherence to these standards are unknown. The objective of this study was to assess the current state of phototherapy practice and to determine if this was in-line with the Indonesian Hyperbilirubinemia Guideline. The study was done in the neonatal care units of Dr. Soetomo Hospital in Surabaya, Indonesia. We evaluated all babies on phototherapy between September 2019 and September 2020. The conformity to core elements in the national guideline was assessed on hyperbilirubinemia management for 89 infants, two-third of these being preterm and low birth weight. One-third of infants were commenced on phototherapy just based on transcutaneous bilirubin measurement. A significant proportion of infants had phototherapy ceased without bilirubin level assessment or confirmation that jaundice had significantly resolved. Almost all (95.9%) of the phototherapy sessions did not conform to guidelines, with the most common being inadequate exposure of the body surface area to light. In spite of a guideline adapted to be pragmatic and applicable to the local setting, healthcare practitioners were not sufficiently aligned, thus an urgent reassessment of the implementation and adoption of the current hyperbilirubinemia guideline is required.